Landscape transformations of a punta a socio-environmental history of purok 3, Punta Dumalag, Brgy. Matina Aplaya, Davao City - Gempesaw, Ian M.
This research study is an attempt to write the history of Purok 3, Punta Dumalag that is tied to or is particularly illuminated in the landscape transformations of the place for the past 50 years. Likewise, part of the study were to (1) explore the factors/agents/ conditions that led to the landscape transformation of the place, (2) describe the landscape conditions of the place historically and at present, and (3) describe the patterns/ changes regarding land-use of the place by humans as well as non-humans historically and at present. The researcher has found out that through the past 50 years, Purok 3, Punta Dumalag had undergone series of landscape transformations: (1) As coconut orchard, (2) log ponds/log yards, (3) settlement area, (4) privately owned/Idle Land, and (5) Marine Turtle sanctuary, although the first two transformations have already been concluded, the next three transformations have remained or are still in existence. On the same note, it can be said that the greatest transformation that Purok 3, Punta Dumalag had undergone was its transformation from an island that was dominated by natural flora and fauna to a reclaimed area or is connected with the rest of Punta Dumalag (Purok 1 & 2) at present. Moreover there are three chief agents of landscape transformations of Purok 3, Punta Dumalag: (1) the Migrants, (2) the Landholders, and (3) the State (in this case the local government). Likewise, it can also be said that the landscape transformations of Purok 3 might have been influenced/ shaped by other factors/agents conditions. Such were market economy, family relations, natural or physical forces (such as geography and tide flow), etc. furthermore, it can be said that historically, before the arrival of settlers in Purok 3, non-humans have dominantly used the innermost shorelines of Purok 3. and upon the arrival of settlers in the area (or in Punta Dumalag), certainly, humans and non-humans have shared in utilizing the area. But accordingly, at present, since more portion of the innermost shorelines of the island had been declared as Marine Turtle Sanctuary (and majority of the innermost portion of the island has been proposed to become a Marine Turtle Protection and Conservation Area), at the end, it suggests that it would still favor non-humans in utilizing the area but with the help of humans. And accordingly, as soon as the elevated portion and some parts of the shorelines of Purok 3 was utilizedby humans, it was turned into an (1) agricultural {by 1950s to 1970s], and (2) industrial [by 1960s to 1980s], and (3) residential [1970s up to present] areas.
Thesis, Undergraduate (BA Social Science) -- U. P. in Mindanao